2022
DOI: 10.1021/acs.analchem.2c01703
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Trace Nanoplastics in Food Packages─An Electrochemical Approach Facilitated by Synergistic Attraction of Electrostatics and Hydrophobicity

Abstract: Most food packages are made of plastics, nanoplastics released from which can be directly ingested and induce serious damage to organisms. Therefore, it is urgent to develop an effective and convenient method for nanoplastic determinations in food packages. In this work, we present a sandwich-based electrochemical strategy for nanoplastic determination. Positively charged Au nanoparticles were coated onto a Au electrode to selectively capture negatively charged nanoplastics in an aqueous environment. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 40 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Previous reports of nanoplastics evidence in real samples such as human blood, human lungs, beverages, drinking water, milk, and food packages were observed. Most of the previous studies have found that majority of the food samples contain micro/nanoplastics with a size range from 5 mm to 700 nm, where PET and PS are the most abundant . Thus, to test the feasibility of the matrix detection of PET nanoplastics in actual environmental water samples, we evaluated the SERS detection of PET nanospheres in tap water and lake water samples.…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports of nanoplastics evidence in real samples such as human blood, human lungs, beverages, drinking water, milk, and food packages were observed. Most of the previous studies have found that majority of the food samples contain micro/nanoplastics with a size range from 5 mm to 700 nm, where PET and PS are the most abundant . Thus, to test the feasibility of the matrix detection of PET nanoplastics in actual environmental water samples, we evaluated the SERS detection of PET nanospheres in tap water and lake water samples.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies must be considered cautiously since the cited polymer is not the most abundant in the environment. The use of PP and PVC NPs, instead, is primarily representative of plastic fragments commonly found, for instance, on the sea surface (5), in sampled lakes, ponds, and surface flooding (30), or in food packages (31).…”
Section: Introductionmentioning
confidence: 99%